2020
DOI: 10.1101/gr.254219.119
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of human long noncoding RNAs via molecular phenotyping

Abstract: Long noncoding RNAs (lncRNAs) constitute the majority of transcripts in the mammalian genomes, and yet, their functions remain largely unknown. As part of the FANTOM6 project, we systematically knocked down the expression of 285 lncRNAs in human dermal fibroblasts and quantified cellular growth, morphological changes, and transcriptomic responses using Capped Analysis of Gene Expression (CAGE). Antisense oligonucleotides targeting the same lncRNAs exhibited global concordance, and the molecular phenotype, meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
162
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(167 citation statements)
references
References 59 publications
3
162
0
Order By: Relevance
“…In the fifth edition of FANTOM (FANTOM5), we constructed ‘atlases’ of promoters ( 3 , 4 ), enhancers ( 5 ), miRNAs ( 6 ) and long non-coding RNAs (lncRNAs) ( 7 ) in several mammalian genomes. Recently, the sixth edition of FANTOM (FANTOM6) was launched to elucidate the biological functions of lncRNAs ( 8 ). LncRNAs constitute a major fraction of the transcriptome and can be broadly categorized into sense-intronic, antisense, intergenic, divergent and enhancer RNA regions ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fifth edition of FANTOM (FANTOM5), we constructed ‘atlases’ of promoters ( 3 , 4 ), enhancers ( 5 ), miRNAs ( 6 ) and long non-coding RNAs (lncRNAs) ( 7 ) in several mammalian genomes. Recently, the sixth edition of FANTOM (FANTOM6) was launched to elucidate the biological functions of lncRNAs ( 8 ). LncRNAs constitute a major fraction of the transcriptome and can be broadly categorized into sense-intronic, antisense, intergenic, divergent and enhancer RNA regions ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the summary of the FANTOM web resource from FANTOM5 and FANTOM6 projects including previously reported and currently updated resources ( 17 , 18 ), as well as newly-released datasets ( 8 , 16 , 17 ). Mainly, we provide new non-coding RNA (ncRNA) resources including the functional annotation of 285 human lncRNAs from the FANTOM6 pilot study ( 8 ), along with the miRNA atlases of rat, dog, chicken and macaque ( 19 ). Each miRNA atlas was also supplemented with computationally-predicted motif activities, genome-wide transcription factor binding sites (TFBS) and multiple genomic alignments of human, mouse, rat, chicken and macaque.…”
Section: Introductionmentioning
confidence: 99%
“…The average mapping rate was 69.5%, with ~500,000 mapped counts obtained on average across all 240 samples. First, expression for CAGE promoters was estimated by counting the numbers of mapped CAGE tags falling under the 379,952 promoter regions of FANTOM 6 CAT gene models (described in [19]). Next, the expression of the corresponding 124,047 genes was estimated by summing up the expression values of all promoters assigned to a given gene.…”
Section: Methods (Protocol)mentioning
confidence: 99%
“…For example, knockdown of MALAT1 using intravenously injected cEt-modified gapmer ASOs in a mouse model of mammary carcinoma resulted in slower tumor growth and reduction in metastasis [17], whereas LNA-modified gapmer ASOs have been used to study the biological functions of the lncRNAs NEAT1 and SAMMSON, respectively [103,131]. A recent study reported on systematic knockdown of 285 lncRNAs in human dermal fibroblasts deploying LNA gapmer ASOs followed by quantification of cellular growth, morphological changes, and transcriptomic responses using capped analysis of gene expression (CAGE) [132]. ASOs targeting the same lncRNAs showed global concordance, and the molecular phenotypes assessed by CAGE recapitulated the cellular phenotypes, while also providing information about the affected pathways [132].…”
Section: Therapeutic Targeting Of Lncrnas For Treatment Of Liver Diseasementioning
confidence: 99%
“…A recent study reported on systematic knockdown of 285 lncRNAs in human dermal fibroblasts deploying LNA gapmer ASOs followed by quantification of cellular growth, morphological changes, and transcriptomic responses using capped analysis of gene expression (CAGE) [132]. ASOs targeting the same lncRNAs showed global concordance, and the molecular phenotypes assessed by CAGE recapitulated the cellular phenotypes, while also providing information about the affected pathways [132].…”
Section: Therapeutic Targeting Of Lncrnas For Treatment Of Liver Diseasementioning
confidence: 99%